Characterization of the transformed jolli-jeep food service operations in Makati City - Ortiz, Paula A. (2004)
The research is a descriptive study about the transformed "jolli-jeep" food services. The units of analysis were small food service operators and customers located in the plush business district of Makati City. Fifty operators and 250 customers were taken as sample respondents. The study was conducted to obtain a characterization of the life and practices of the food operators in the conduct of their business operations. A profile of the customers and their perception on the food and service of these micro-businesses were obtained. Interviews and self-accomplished questionnaires were used to gather data. Findings showed that majority of the operators were married females with dependent children, middle-aged and highschool graduates. The present operators were in this type of business as a result of the influence of their families, who were also engaged in similar occupations. Majority worked fulltime in the food services, hence sought help from relatives and kinsmen as coping mechanisms for their households. The start-up capital was at least Php 10,000 and sourced from their personal savings. The "jolli-jeep" were open from Monday to Saturday and had sales averaging Php 6,500. The operators used cycle menus, with caldereta and liempo as popular specialties. The selling price range was from Php 16- Php 33. Materials were purchased mainly from formal and informal suppliers. Most of them practiced pre-preparation at home. Frying, boiling and sauteing were the preferred and frequently used cooking methods. "Turo-turo", choosing from a variety of foods using the point finger; "standing-eating", dining without need for tables and chairs; and "balot-balot", meals packed in plastic bags or styro were unique and convenient ways to serve customers. Tap water, filtered or not as well as mineral water were sources of drinking water. The latter types were sold. The work space allotted for each trailer was deemed inadequate by the sellers. Almost all have attended one or more food service training seminars. Demographics showed that customers were mostly male, young, single and married with salaries above the minimum wage. The customers were satisfied with the food and service, underlining convenience as the main reason. The transformed "jolli-jeep" food service is considered unique. The set-up of the operations was informal but served a large number and has its role in contributing to the economy. This phenomenon is a unique representation of low-status food served in a particular segment of the market yet located within a high status environment. Family integrity among the vendors is preserved by making the business a family affair with members being in the selling place as much as possible. Otherwise, the extended family becomes convenient with relatives helping in caring for children left at home. Communication is maintained especially with the use of cellphone. The problems encountered by the operators were mainly on budget constraints and restrictive policies of the contractor. The food service operational aspect that needed much improvement is the housekeeping and/or maintenance of the stalls. The study recommends that facilities and maintenance should be a concern for both parties. There should be strict implementation of waste segregation, use of food holding equipment and sneezeguard. The local government could help provide financial assistance by linking "jolli-jeeps" operators with micro-scale lending institutions. There should be a constant dialogue between operators and vendors to thresh out unclear policies. To promote this unique type of food service and tourism in the locale, holding a "streetfood festival" is recommended showcasing the different regional dishes and delicacies of the country. In relation to preserving family integrity, the local government, various institutions within the church, or the Department of Social Welfare and Development, Non-Government Organizations could initiate programs or seminars in support of preservation of family values.